2020
DOI: 10.1177/0954407020924981
|View full text |Cite
|
Sign up to set email alerts
|

A design approach for multi-configuration hybrid transmission mechanisms

Abstract: Several hybrid architectures have been widely used in hybrid electric vehicles. For example, power-split architecture brings seamless operation, while parallel architecture makes the internal combustion engine directly drive the wheel. To combine the advantages of various architectures, this study aims to develop a design approach to create a transmission mechanism that has multiple configurations and uses these configurations to achieve several hybrid architectures. First, this study standardized hybrid trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
(34 reference statements)
0
1
0
1
Order By: Relevance
“…One of the possibilities to avoid this is by allowing flexible power flow configurations in the powertrain. Studies [24][25][26] support this argument, where it is found that the powertrain efficiency and driving performance (in terms of acceleration time and comfort) can be optimized for the full EV driving experience if the driving loads can be properly distributed to two electric motors in the powertrain configuration with different transmission ratios. In the study, the possibility of implementing different hybrid EV (HEV) powertrain configurations was evaluated, and the configuration was defined in terms of coupling between the motors to the ICE, and also in terms of different transmission ratios.…”
Section: Optimizing Power Flow In Ev Powertrainsmentioning
confidence: 92%
“…One of the possibilities to avoid this is by allowing flexible power flow configurations in the powertrain. Studies [24][25][26] support this argument, where it is found that the powertrain efficiency and driving performance (in terms of acceleration time and comfort) can be optimized for the full EV driving experience if the driving loads can be properly distributed to two electric motors in the powertrain configuration with different transmission ratios. In the study, the possibility of implementing different hybrid EV (HEV) powertrain configurations was evaluated, and the configuration was defined in terms of coupling between the motors to the ICE, and also in terms of different transmission ratios.…”
Section: Optimizing Power Flow In Ev Powertrainsmentioning
confidence: 92%
“…Đặc biệt ở Việt Nam, hệ thống trạm sạc điện chung chưa đáp ứng được nhu cầu phát triển của xe EV. Chính vì vậy, xe HEV với việc sử dụng phối hợp hai nguồn động lực của động cơ điện (ĐCĐ) và ĐCĐT được đánh giá là giải pháp phù hợp với tình hình hiện nay tại Việt Nam [8], [9]. Do xe HEV có công nghệ rất phức tạp cả về kết cấu và hệ thống điều khiển, nên việc sử dụng, bảo dưỡng gặp rất nhiều khó khăn.…”
Section: Hình 1 Tỷ Lệ đóNg Góp Phát Thải Các Chất Gây ô Nhiễm Không K...unclassified